Guggulsterone enhances head and neck cancer therapies via inhibition of signal transducer and activator of transcription-3 - Leeman-Neill, Rebecca J. (Oxford University Press, 2009)
Treatment of human head and neck squamous cell carcinoma (HNSCC) cell lines with guggulsterone, a widely available, well-tolerated nutraceutical, demonstrated dose-dependent decreases in cell viability with EC(50)s ranging from 5 to 8 μM. Guggulsterone induced apoptosis and cell cycle arrest, inhibited invasion and enhanced the efficacy of erlotinib, cetuximab and cisplatin in HNSCC cell lines. Guggulsterone induced decreased expression of both phosphotyrosine and total signal transducer and activator of transcription (STAT)-3, which contributed to guggulsterone's growth inhibitory effect. Hypoxia-inducible factor (HIF)-1α was also decreased in response to guggulsterone treatment. In a xenograft model of HNSCC, guggulsterone treatment resulted in increased apoptosis and decreased expression of STAT3. In vivo treatment with a guggulsterone-containing natural product, Guggulipid, resulted in decreased rates of tumor growth and enhancement of cetuximab's activity. Our results suggest that guggulsterone-mediated inhibition of STAT3 and HIF-1α provide a biologic rationale for further clinical investigation of this compound in the treatment of HNSCC.